Goal Adjustment and Well-Being: The Role of Optimism in Patients with Chronic Pain. Issue 7 (3rd September 2018) - Ramírez-Maestre, Carmen; Esteve, Rosa; López-Martínez, Alicia E; Serrano-Ibáñez, Elena R; Ruiz-Párraga, Gema T; Peters, Madelon
Abstract: Background: Chronic pain directly or indirectly interferes with valued personal goals. Goal adjustment plays a central role in patients' adaptation. Studies on the relationship between optimism and goal regulation have shown that people with high dispositional optimism adjust their goals in a flexible way, and that flexible goal adjustment promotes quality of life. Purpose: The aim of this study was to analyze the relationship among optimism, goal adjustment, and adaptation in patients with chronic pain. Methods: A sample of 258 patients with chronic musculoskeletal pain completed questionnaires on optimism, reengagement, disengagement, flexibility, tenacity, rumination, purpose in life, well-being, pain intensity, daily functioning, and impairment. Results: Structural equation modeling analysis showed that optimism had a positive association with reengagement, flexibility, and tenacity, and a negative association with disengagement. Disengagement was positively associated with rumination, whereas reengagement, flexibility, and tenacity were associated with higher levels of purpose in life, which were strongly associated with adaptation in patients with chronic pain. Conclusions: This study supports the conclusions of previous research on the role of goal adjustment as a mediator variable between optimism and well-being. Abstract : The relationship between optimism and the successful adaptation of patients with chronic pain is mediated by the effectiveness of goal adjustment strategies and the levels of purpose in life.